Meta-Analysis of Risk Stratification of SCN5A With Brugada Syndrome: Is SCN5A Always a Marker of Low Risk? - Yang, Yihan; Hu, Dan; Sacher, Frederic; Kusano, Kengo F.; Li, Xinye; Barajas-Martinez, Hector; Hocini, Mélèze; Li, Yanda; Gao, Yonghong; Shang, Hongcai; Xing, Yanwei (Frontiers in Physiology, 2019)
Background: SCN5A with Brugada syndrome (BrS) is not commonly considered as an independent risk marker for subsequent cardiac events. However, the risk of SCN5A combined with other clinical characteristics has not been fully investigated. Objectives: The aim of this study is to investigate and evaluate risk stratification and related risk factors of SCN5A in BrS. Methods: The databases of PubMed, EMBASE, Cochrane Library, MEDLINE, Chinese National Knowledge Infrastructure (CNKI) and Wanfang Data were searched for related studies published from January 2002 to May 2018 followed by meta-analysis. The BrS patients who underwent SCN5A gene tests were included. The prognosis and risk stratification of SCN5A combined with symptoms and asymptoms diagnosis in BrS, electrophysiology study (EPS) were then investigated and evaluated. Outcomes were defined as ventricular tachycardia/fibrillation （VT/VF）, sudden cardiac death (SCD). Results: Eleven suitable studies involving 1892 BrS patients who underwent SCN5A gene tests were identified. SCN5A (+) was not considered to be a significant predictor of future cardiac events (95% CI: 0.89–2.11; P = 0.15; I2 = 0%). However, SCN5A (+) patients with symptoms at diagnosis revealed a higher prevalence of future VT/VF,SCD compared to SCN5A (-) patients with symptoms at diagnosis. (95% CI: 1.06-3.70; P = 0.03 I2 = 0 %) Among asymptomatic patients, the risk did not significantly differ between SCN5A (+) patients and SCN5A (-) patients. (95% CI: 0.51-4.72; P = 0.45 I2 = 0 %). In an investigation involving patients in EPS(-) BrS electrocardiogram (ECG), the risk of SCN5A (+) is higher than that of SCN5A (-) (P < 0.001). Conclusions: In BrS patients with symptoms at diagnosis or EPS(-), the meta-analysis suggests that SCN5A (+) are at a higher risk of arrhythmic events than SCN5A (-).